Hybridization or Salad Bar Ideology? Testing Ideological Convergence Within the American Violent Far Right - Hemmila, Tess (Crime & delinquency, 2025)
In September 2020, FBI Director Christopher Wray described far-right extremist motivations as “a mishmash” or “salad bar” of ideologies. Academics and practitioners have further promoted such ideas using case studies of inter-organizational collaboration. The current study tests the “Salad Bar” and Hybridization hypotheses by analyzing the online discourse of far-right extremist groups to identify similarities and differences in their designation of “adversaries,” topics of political discourse, support for violence, membership characteristics, and psychological dimensions. After computer-assisted analysis of ideological discourse samples, our findings indicate that there may be an initial overlap between far-right groups, but it is too early to assume hybridization across the far-right.